2009
DOI: 10.1037/a0017218
|View full text |Cite
|
Sign up to set email alerts
|

What research tells us about the intersecting streams of homelessness and foster care.

Abstract: This paper reviews mounting evidence linking foster care and homelessness and considers new approaches for intervention. Although there is no causal evidence that family homelessness leads to foster care or vice versa, the association no longer originates solely from samples of homeless people, but also from samples of people with childhood histories of foster care. Many programs work with families, children or youth based on their current living situations and limits imposed by funders. This results in discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…Contrasting historical and post-2006Á2007 data on H/HM students with a NonMobile population of students in the same school districts over the same time period provided evidence, consistent with previous research (Culhane et al 2003;Zlotnick 2009), that H/HM students have significantly more involvement with child welfare prior to an identification of homelessness or high mobility by the schools. H/HM students also exhibit falling attendance trajectories prior to the year of their identification.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Contrasting historical and post-2006Á2007 data on H/HM students with a NonMobile population of students in the same school districts over the same time period provided evidence, consistent with previous research (Culhane et al 2003;Zlotnick 2009), that H/HM students have significantly more involvement with child welfare prior to an identification of homelessness or high mobility by the schools. H/HM students also exhibit falling attendance trajectories prior to the year of their identification.…”
Section: Discussionsupporting
confidence: 87%
“…Bassuk and Rosenberg (1997) found that by the age of 8 years, one in three children who are homeless have a diagnosable mental disorder. Children who are homeless are also more likely to be involved with child welfare (Culhane et al 2003;Zlotnick 2009). …”
Section: Introduction: Students Who Are Homelessmentioning
confidence: 98%
“…Once homeless or “drifting”, street culture promotes antisocial behavior, including association with deviant peers and means of subsistence (e.g., sex trade, theft, drug dealing) [11]. The cumulative impact of these factors places youth at high risk for a wide range of health and psychosocial problems including substance misuse and chronic homelessness [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of homelessness, unemployment, mental health issues, and incarceration have been found for these adolescents (Dregan & Gulliford, 2012;Dworsky & Courtney, 2009;Stott, 2012). Studies show adolescents both in and aging out of foster care to be more at risk for engaging in risky sexual behaviors, teen pregnancy, participating in self-destructive and delinquent behaviors (Fowler, Toro, & Miles, 2009;Grogan-Kaylor et al, 2008;Zlotnick, 2009). Indeed, increasing age has been found to be associated with a higher risk of substance use (Guibord, Bell, Romano, & Rouillard, 2011).…”
Section: Risks Of Substance Use For Adolescents In Foster Carementioning
confidence: 93%